Congenital syphilis in Argentina: Experience in a pediatric hospital - García, Luciana Noemí (2021)
In spite of being preventable, Congenital syphilis (CS) is still an important, and growing health problem worldwide. Fetal infection can be particularly aggressive, but newborns can be asymptomatic at birth and, if left untreated, develop systemic compromise afterwards with poor prognosis. We analyzed 61 CS diagnosis cases between 1987–2019 presenting at the Buenos Aires Children’ Hospital. The distribution of cases showed a bimodal curve, with a peak in 1992–1993 and in 2014–2017. Median age at diagnosis was 2 months (IQ 1–6 months). The main clinical findings were: bone alterations (59%); hepatosplenomegaly (54.1%); anemia (62.8%); skin lesions (42.6%) and renal compromise (33.3%). Cerebrospinal fluid (CSF) was abnormal in 5 patients, normal in 45 and was not available for 11 patients. Remarkably, spinal lumbar puncture did not modify therapeutic decisions in any case. Between mothers, only 46% have been tested for syphilis during pregnancy and 60.5% patients had non-treponemal titers equal to or less than fourfold the maternal titer. Intravenous penicillin G was prescribed for all except one patient, who received ceftriaxone with good therapeutic response. During follow-up, 1.6% infants died, 6.5% had persistent kidney disorders and 1.6% showed bone sequelae damage. RPR titers decreased after treatment, reaching negative seroconversion in 43% subjects at a median of 26.4 months. Low adherence to follow up was observed due to inherent vulnerable and low-income population characteristics in our cohort. Our results highlight a rising tendency in cases referred for CS in our population with high morbidity related to delayed diagnosis. A good therapeutic response was observed. CS requires a greater effort from the health system to adequately screen for this disease during pregnancy, and to detect cases earlier, to provide an adequate diagnosis and treatment.